Potassium channel openers and vascular smooth muscle relaxation - Edwards, G; Weston, A H (Pharmacology & therapeutics (Oxford), 1990)
Potassium channel openers comprise a diverse group of chemical agents which open plasma-lemmal K-channels. They show selectivity for smooth muscle, although K-channels in cardiac and skeletal muscle, neurones and the pancreatic beta-cell are also affected at relatively high concentrations. In addition, at least one endogenous K-channel opener of vascular origin--endothelium-derived hyperpolarizing factor--exists and in man plays a role in modulating blood vessel tone. The type of K-channel involved in the actions of both exogenous and endogenous K-channel openers is still uncertain, although a prime candidate in smooth muscle seems similar to the [ATPi]-modulated K-channel in the pancreatic beta-cell. This review focuses attention on the action of these agents in vascular smooth muscle and on the possible clinical exploitation of their powerful vasorelaxant properties.